O demoníaco no protestantismo: analisando a representação do diabo em Lutero e Calvino – século XVI - Lima, Eduardo Leote de (2021)
The present work comprehends the representation of the Devil in the 16th century from the works of two Protestant authors: Martin Luther (1483-1546) and John Calvin (1509- 1564). Our objective is to analyze the process of individualization of the logic of salvation in the period and the consequent absorption of the diabolic figure into our conscience, listing how this phenomenon was closely linked with others, such as the establishment of patterns of behavior, the control and the self-control of consciences and bodies, the establishment of power relations, and the birth of modernity itself. In this way, a research is carried out from a comparative and at the same time complementary approach to the sources, that is, to analyze them in order to understand which form the Devil is represented in each one and how they, together, help in the construction than was the idea of Demon at the time. At the same time, an approach is sought that represents an interdisciplinarity between the areas of history and psychology, in order to consider the Devil as the fruit of the very historical conditions of his creation at the same time that he sees him as cognitive responses to the pressures of the environment. Thus, we work with a theoretical and methodological tool that brings together Cultural History, especially the concepts of representation and speech, by Roger Chartier, as well as areas of Social Psychology, such as the case of Casual Attribution, and the Cognitive Science of Religion, with the evolutionary psychology. The research is part of the research line Border, Politics and Society, of the Postgraduate Program in History of the Federal University of Santa Maria (PPGH-UFSM), at the master’s level.